PERAN SUPERVISI KEPALA MADRASAH DALAM MENINGKATKAN MUTU PENDIDIKAN (Studi Kasus di MTsN 1 Jombang) - Zainal Arifin (PASCASARJANA UNISNU, 2022)
Education is a strategic tool to improve the degree of human life, through education, humans have a good life character. Improving the quality of an education is the hope of all nations, the head of the madrasa is the highest person in charge of the institution, who has duties and responsibilities for the quality of education. One of the ways to provide guidance is through the supervision of the Madrasah Head. Supervision of the Head of Madrasah serves to help teachers develop their abilities in managing the learning process. This research focuses on 3 aspects, namely: first, how to design the supervision of the head of madrasah in improving the quality of education, second, how to implement the supervision of the head of madrasah in improving the quality of education, third, the inhibiting and supporting factors in the implementation of the supervision of the head of madrasah in improving the quality of education. quality of education. This research approach is descriptive qualitative research type case study, interview data collection techniques, observation, and documentation. Data analysis techniques through data reduction, data presentation, and drawing conclusions/verification. Checking the validity of the data is done through data credibility, transferability, dependability, and confirmability.